2022
DOI: 10.1155/2022/7291774
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin Gallate Relieved PM2.5-Induced Lung Fibrosis by Inhibiting Oxidative Damage and Epithelial-Mesenchymal Transition through AKT/mTOR Pathway

Abstract: Oxidative damage and epithelial-mesenchymal transition (EMT) are main pathological processes leading to the development of PM2.5-induced lung fibrosis. Epigallocatechin gallate (EG), a natural polyphenol extracted from green tea, possesses the ability to combat oxidative stress and inflammation. However, the potential roles of EG in PM2.5-induced lung fibrosis have not been reported yet. In the present study, we investigated whether EG could relieve PM2.5-induced lung injury and fibrosis in vivo and in vitro. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…A number of studies have illustrated the anti-fibrotic effects of EGCG in the liver [ 77 ], kidney [ 78 ], lungs [ 79 ], heart [ 80 ] and other organs. Treatment with EGCG in isolated uterine fibroid or myometrial cells resulted in the reduction in mRNA or protein levels of critical fibrotic markers including fibronectin, collagen I, plasminogen activator inhibitor-1 (PAI-1), CTGF and α-SMA [ 81 ].…”
Section: Major Plant-derived Compounds That Modulate Fibrosismentioning
confidence: 99%
“…A number of studies have illustrated the anti-fibrotic effects of EGCG in the liver [ 77 ], kidney [ 78 ], lungs [ 79 ], heart [ 80 ] and other organs. Treatment with EGCG in isolated uterine fibroid or myometrial cells resulted in the reduction in mRNA or protein levels of critical fibrotic markers including fibronectin, collagen I, plasminogen activator inhibitor-1 (PAI-1), CTGF and α-SMA [ 81 ].…”
Section: Major Plant-derived Compounds That Modulate Fibrosismentioning
confidence: 99%
“…EMT is identified by a decrease in epithelial markers of tight junctions, such E-cadherin, and an increase in mesenchymal markers such as alpha smooth muscle actin (a-SMA) and vimentin. Several recent studies have reported changes in these markers following PM-exposure (Chen et al, 2020;Liu et al, 2022a;Pan et al, 2021;Saha et al, 2022;Wang et al, 2022d;Zhongyin et al, 2022), but only one clearly demonstrated the cascade of events, from ROS generation to NF-kB activation to EMT induction, using antioxidants and an NF-kB inhibitor (Chen et al, 2020). The transforming growth factor beta 1 (TGF-b1) is yet another important player in EMT-mediated airway remodeling induced by PM exposure.…”
Section: Activation Of the Inflammatory Response And Its Consequencesmentioning
confidence: 99%
“…Ephedrine (an alkaloid), (-)-epicatechin and biochanin A (flavonoids), and glycyrrhizin (a saponin) proved to have similar Nfr2 induction activity that helped bronchial and alveolar epithelial cells counteract the PM-induced cytotoxic effects (Shi et al, 2023;Tian et al, 2021;Wang et al, 2022a;Xue et al, 2021b). The green tea derived polyphenols gallocatechin gallate and epigallocatechin gallate have demonstrated their antioxidant activity to counteract PMinduced oxidative potential in vitro, possibly by inhibiting the protein kinase B/ mammalian target of rapamycin (Akt/mTOR) pathway, therefore alleviating oxidative stress and EMT induced by PM (Tanaka et al, 2022;Zhongyin et al, 2022). Treatment with antioxidants based on traditional Chinese and Northeast Asian medicine, such as Tiaobu Feishen formulae, effective-component compatibility of Bufei Yishen formula (ECC-BYF), and Citrus junos peel extracts have also shown to be effective in overcoming PM-induced oxidative stress (Haoran et al, 2020;Lee et al, 2022a;Li et al, 2021).…”
Section: Compounds With Antioxidant Activity Against Pm-induced Oxida...mentioning
confidence: 99%